(untitled) (Scientific journal of the Fergana State University, 2023)
The article covered the topic of holding a large amount of support for the protection of the family, mothers and children. In our country it has been carried out advanced work on the state year program “A healthy mother and a child”. The aim of the program is socio-material and spiritual welfare and protection of the family.